Companion cell-specific inhibition of the potato sucrose transporter SUT1 - Sonnewald, Uwe; et al. (Plant Cell and Environment, 1996)
In many plants, translocation of sucrose from mesophyll to phloem for long-distance transport is carrier-mediated. The sucrose H+-symporter gene SUT1 from potato is expressed at high levels in the phloem of mature, exporting leaves and at lower levels in other organs. Inhibition of SUT1 by expression of an antisense gene in companion cells under control of the rolC promoter leads to accumulation of high amounts of soluble and insoluble carbohydrates in leaves and inhibition of photosynthesis. The distribution of in situ localized starch does not correspond with areas of reduced photosynthesis as shown by fluorescence imaging. Dissection of antisense effects on sink and source organs by reciprocal grafts shows that inhibition of transporter gene expression in leaves is sufficient to produce chlorosis in leaves and reduced tuber yield. In contrast to the arrest of plasmodesmal development found in plants that express yeast invertase in the apoplast, in mature leaves of sucrose transporter antisense plants plasmodesmata are branched and have median cavities. These data strongly support an apoplastic mode of phloem loading in potato, in which the sucrose transporter located at the plasma membrane of the sieve element/companion cell complex represents the primary route for sugar uptake into the long-distance translocation pathway.
Keywords: Solanum tuberosum L; apoplastic phloem loading; proton cotransport; rolC promoter; sink-to-source transition